2014
DOI: 10.1016/j.joi.2013.10.007
|View full text |Cite
|
Sign up to set email alerts
|

The competitive advantage of nations: An application to academia

Abstract: Within the field of bibliometrics, there is sustained interest in how nations "compete" in terms of academic disciplines, and what determinants explain why countries may have a specific advantage in one discipline over another. However, this literature has not, to date, presented a comprehensive structured model that could be used in the interpretation of a country's research profile and academic output. In this paper, we use frameworks from international business and economics to present such a model. Our stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 41 publications
(43 reference statements)
2
52
0
3
Order By: Relevance
“…Additionally, an economic approach was also used by these authors, who observed that high-income countries were the core group in international collaboration and that they tend to be the main partner of other types of countries. Interestingly, in our study the highest percentage of papers in collaboration with low R&D countries is found in Agriculture and Chemistry (29 and 33 % respectively), maybe because Spain is a particularly ''attractive'' partner for low R&D countries in these fields in which it shows a high specialisation or revealed comparative advantage (Harzing and Giroud 2014).…”
Section: High and Low Randd Partnersmentioning
confidence: 49%
See 1 more Smart Citation
“…Additionally, an economic approach was also used by these authors, who observed that high-income countries were the core group in international collaboration and that they tend to be the main partner of other types of countries. Interestingly, in our study the highest percentage of papers in collaboration with low R&D countries is found in Agriculture and Chemistry (29 and 33 % respectively), maybe because Spain is a particularly ''attractive'' partner for low R&D countries in these fields in which it shows a high specialisation or revealed comparative advantage (Harzing and Giroud 2014).…”
Section: High and Low Randd Partnersmentioning
confidence: 49%
“…The examination of this set of papers allows us to identify Italy and China as the most beneficial partners (RCR [1 in both cases) and it is interesting to note that both countries show high specialisation in Mathematics, that is, their share of publications in the field is higher than in all science fields (Harzing and Giroud 2014). Furthermore, among the low R&D countries that more often collaborate with Spain, Latin America is prominent as a regional partner (Brazil, Argentina and Mexico) probably for language-sharing reasons, along with a number of Eastern European Countries, such as Poland, Hungary, Romania or Ukraine, which have been described as specialised in Mathematics (Glänzel 2001;Harzing and Giroud 2014). Among low R&D countries the collaboration with Romania and Ukraine shows a particularly high impact, which again points at the positive effect of specialised partners.…”
Section: Factors Influencing Research Impactmentioning
confidence: 99%
“…Pouris and Ho (2014) used AI to identify the emphasized and underemphasized research fields of Africa. Harzing and Giroud (2014) used AI to discover the competitive advantages of nations for different academic disciplines.…”
Section: Methodsologymentioning
confidence: 99%
“…As such, despite the criticism, the PDM has been used to evaluate competitive advantage in various industries and countries. In higher education (HE), the PDM has been used to investigate several aspects, including research competitiveness (Curran, 2000); Countries' comparative advantages in academic disciplines (Harzing and Giroud, 2014); and the competitiveness of the national HE systems (Stonkiene et al, 2016). Nevertheless, the PDM has not been used in the context of TNE, and from the TNE exporting country/institution's perspective, to evaluate a TNE host country as export destination.…”
Section: The Role Of Government and Chancementioning
confidence: 99%